Grants & consultation projects - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2021)
Congratulations to the researchers on their achievements in securing high-impact research grants and consultancy projects. Ts. Dr. Ismaniza Ismail, together with team members from the Faculty of Health Sciences, received RM250,000 from the Department of Occupational Safety and Health, Ministry of Human Resources to conduct a study on the profile and development of guidelines for occupational mental health management in the workplace. Dr. Nur Nadiah Md Yusof, as project leader, along with Associate Professor Dr. Asmida Ismail, Dr. Faezah Pardi, and Dr. Siti Khairiyah Hatta, was awarded a consultancy project valued at RM93,969 from the Department of Wildlife and National Parks (PERHILITAN) Peninsular Malaysia for the preparation of guidelines on wildlife cultivation. In addition, Ts. Dr. Rosdiyana Hasham@Hisam, in collaboration with researchers from UPSI, UPM, and USM, received the UTM–UiTM Strategic Research Partnership Grant amounting to RM80,000 for a project focused on improving the bioactivity and mechanical properties of zirconium mesoporous borosilicate bioactive glass/PCL/PLA scaffolds. These accomplishments reflect a strong commitment to advancing research excellence and contributing expertise for national and societal development.